The final score [compact disc, unabridged] - Winslow, Don, 1953- (HarperCollins Publishers, 2025)
In six all-new short novels written with the trademark literary style, trenchant wit, and incisive characterization that have made Don Winslow 'America's greatest living crime writer', the repeat New York Times bestselling author serves up a collection of tales sure to delight Winslow's most devoted fans and first-time listeners.